Urogenital Fistulas in Women: 5-year Experience at a Single Center - Singh, Onkar; Gupta, Shilpi Singh; Mathur, Raj Kumar (Urology Journal, 2010)
Introduction: Urogenital fistula is one of the most devastating complications that can result from labor or urogenital surgeries. It is still a frequent problem in the developing world. Urogenital fistulas can lead to devastating medical, social, and psychological problems; thus cause major impact on the lives of girls and women. However, these cases are still largely neglected in the developing world. We aimed to evaluate causative factors and discuss management of urogenital fistulas. Materials and Methods: Forty-two cases of urogenital fistula developing within 5 to 38 days after delivery, pelvic surgery, and obstetric procedures were treated over a period of 5 years from 2003 to 2008. These included 37 vesicovaginal fistulas (88.1%), 4 uterovesical fistulas (9.5%), and 1 pure ureterovaginal fistula (2.4%). All of the patients were catheterized immediately on presentation and the catheter was left in situ for a minimum of 3 weeks before surgical intervention.Results: The most common cause of vesicovaginal fistulas was obstructed labor, while other varieties of fistulas were mostly associated with pelvic surgery. Spontaneous closure occurred in 3 cases of vesicovaginal fistula. Surgical intervention needed in 39 patients. Peritoneal flap and Martius flap were interposed between suture lines in transabdominal and transvaginal approaches, respectively. Thirty-four fistulas (80.1%) were closed at the first attempt. There was no mortality from the surgical procedure.Conclusion: Vasicovaginal fistula is the most common urogenital fistula. Obstructed labor and its complications are still the leading cause of its development. Peritoneal flap interposition technique is a successful and effective treatment method for urogenital fistula.